2013
DOI: 10.1371/journal.pone.0078297
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Body Size, Antennal Size and Host Use in Parasitoid Wasps (Hymenoptera: Chalcidoidea): A Phylogenetic Comparative Analysis

Abstract: Chalcidoid wasps represent one of the most speciose superfamilies of animals known, with ca. 23,000 species described of which many are parasitoids. They are extremely diverse in body size, morphology and, among the parasitoids, insect hosts. Parasitic chalcidoids utilise a range of behavioural adaptations to facilitate exploitation of their diverse insect hosts, but how host use might influence the evolution of body size and morphology is not known in this group. We used a phylogenetic comparative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…In parasitoid wasps, our knowledge of host-range evolution is very limited due to a lack of reliable host records in many groups and lack of robust species-level phylogenies (Quicke, 1997;Quicke, 2012). Recent molecular studies have advanced our knowledge of host-use evolution in a phylogenetic framework (Symonds and Elgar, 2013;Taekul et al, 2014;Tschopp et al, 2013), but few studies have specifically addressed the diversification of parasitoids.…”
Section: Evolution Of Host Use In Pompilinae and Its Correlation Withmentioning
confidence: 99%
“…In parasitoid wasps, our knowledge of host-range evolution is very limited due to a lack of reliable host records in many groups and lack of robust species-level phylogenies (Quicke, 1997;Quicke, 2012). Recent molecular studies have advanced our knowledge of host-use evolution in a phylogenetic framework (Symonds and Elgar, 2013;Taekul et al, 2014;Tschopp et al, 2013), but few studies have specifically addressed the diversification of parasitoids.…”
Section: Evolution Of Host Use In Pompilinae and Its Correlation Withmentioning
confidence: 99%
“…The first of these findings, that breeding strategy is of higher relevance, is rather surprising, as diet breadth (host specificity) has traditionally received much more research attention as an explanatory variable in ecological studies (cf. Davis et al., ; Symonds & Elgar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Females of geometrids have simple, filiform antennae, as do males in some species, whereas in other species, males have feathery (pectinate or plumose) antennae. The ecological basis for such a dichotomy in antennal form among males (present also in several other moth families) is still poorly understood, but antennal size, both total length and length of the setae on feathery antennae, can be assumed to reflect sensory capacity of these organs (Allen, Zwaan, & Brakefield, ; Loudon & Koehl, ; Symonds & Elgar, ; Symonds, Johnson, & Elgar, ). Certainly, other antennal features are of significance (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, several studies have shown that the morphological characteristics of adults and fecundity of female parasitoids are affected by host characteristics, for example, host species (Nicol et al, 1999), host life stage (Traynor et al, 2005), host instars (Cloutier et al, 2000), and host size (Harvey et al, 2006; Mackauer et al, 2001). The size and species of hosts have been shown to greatly influence the evolutionary history of morphological characteristics in parasitoids (Brandl et al, 1987; Belshaw et al, 2003; Charnov et al, 1984; Bakker K et al, 1985; Moore et al, 2002; Symonds et al, 2013). It has been hypothesized that host-parasitoid co-evolution could eventually lead to increased fitness of parasitoids allowing them to parasitize multiple species (Charnov et al,1984; Ellers et al, 2002; Sampaio et al, 2008).…”
Section: Introductionmentioning
confidence: 99%